INFLUENCE OF THE ORIGINAL STATE OF THE LEFT VENTRICLE AND TECHNICAL FEATURES OF CORONARY ARTERY BYPASS SURGERY ON THE FUNCTIONAL SAFETY OF GRAFTS - N. S. Lisyutenko; N. A. Morova; V. N. Tsekhanovich (Евразийский Кардиологический Журнал)
The goal of research is to study the influence of the initial state of left ventricular myocardium, as well as the technical features of the coronary artery bypass graft (CABG) on the prognosis of the functioning of coronary shunts.Materials and methods. 46 men, who had CABG for stable angina class III, were examined. 23 of them had 2 type diabetes mellitus (DM2), 23 of them did not have carbohydrate metabolism disorders. On the eve of the surgery, all patients underwent transthoracic echocardiography to determine the indicators of left ventricular function. Information about the technical features of the CABG were taken from the surgical reports. One year after the surgery, all patients underwent a coronary and bypass angiography.Results. Occlusion of coronary shunts was detected in 10 patients with DM2, and in 6 patients without DM2 (p value for Fisher’s exact test is 0.177). A larger left ventricle end-diastolic and end-systolic diameter (p value for the Mann-Whitney test is 0.004; 0.012), as well as a larger left ventricle end-diastolic and end-systolic volume (p value for the Mann-Whitney test is 0.012; 0.006) were associated with the presence of coronary shunt occlusions in patients with DM2. Also in the group of patients with DM2, sequential venous shunts were significantly more frequently occluded (p value for Fisher’s exact test is 0.004). Dysfunctioning shunts were associated with abovementioned figures among patients without carbohydrate metabolism disorders.Conclusion. The results of the research confirm the mutual confounding influence of risk factors on the prognosis after CABG